2021
DOI: 10.1002/bimj.202100046
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel structural equation model for assessing a drug effect on a patient‐reported outcome measure in on‐demand medication data

Abstract: We analyze data from a clinical trial investigating the effect of an on-demand drug for women with low sexual desire. These data consist of a varying number of measurements/events across patients of when the drug was taken, including data on a patient-reported outcome consisting of five items measuring an unobserved construct (latent variable). Traditionally, these data are aggregated prior to analysis by composing one sum score per event and averaging this sum score over all observed events. In this paper, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Furthermore, when applying the ML‐MIMIC model in practice, it is important to verify the measurement invariance assumptions. In ML‐MIMIC models, invariance of factor loadings and intercepts across groups is implicitly assumed (as was the case in our simulations), but it is advised to test these strict assumptions (Kessels et al., 2021; Kim et al., 2015), in order to ensure that unbiased covariate effects are obtained. Research has shown that in situations where the measurement invariance assumption is partly violated (some but not all intercepts and/or factor loadings are invariant), covariate effects are still unbiased as long as the model is corrected for the invariant parameters (Hsiao & Lai, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, when applying the ML‐MIMIC model in practice, it is important to verify the measurement invariance assumptions. In ML‐MIMIC models, invariance of factor loadings and intercepts across groups is implicitly assumed (as was the case in our simulations), but it is advised to test these strict assumptions (Kessels et al., 2021; Kim et al., 2015), in order to ensure that unbiased covariate effects are obtained. Research has shown that in situations where the measurement invariance assumption is partly violated (some but not all intercepts and/or factor loadings are invariant), covariate effects are still unbiased as long as the model is corrected for the invariant parameters (Hsiao & Lai, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of response shift should therefore also be investigated in ML‐MIMIC models and it has been shown that response shift plays a role in studies using patient reported outcomes, such as quality of life outcomes in cancer studies (Ilie et al., 2019). However, how to deal with these possible measurement invariance violations is beyond the scope of this study and we refer for this to other work (Carlier et al., 2019; Kessels et al., 2021; Kim et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the data are poor-as when there is no validity evidence supporting scores-the most sophisticated data analysis will remain susceptible to incorrect conclusions and inaccurate estimates (Flake, 2021). Weaknesses of unsubstantiated sum scoring have been demonstrated with advanced statistical approaches such as regression discontinuity (Soland et al, 2022), machine learning (Jacobucci & Grimm, 2020), intensive longitudinal data and time-series analysis (McNeish et al, 2021), growth modeling (Kuhfeld & Soland, 2022), network modeling (Haslbeck et al, 2022), and clinical trials (Kessels et al, 2021). More simply, the quality of the statistical model is limited by the quality of the data itself and no statistical workaround can avoid consequences of poor measurement.…”
Section: Policy Implicationsmentioning
confidence: 99%